Huanglongbing: An overview of a complex pathosystem ravaging the world's citrus. Issue 4 (15th December 2015) - da Graça, John V.; Douhan, Greg W.; Halbert, Susan E.; Keremane, Manjunath L.; Lee, Richard F.; Vidalakis, Georgios; Zhao, Hongwei
Abstract: Citrus huanglongbing (HLB) has become a major disease and limiting factor of production in citrus areas that have become infected. The destruction to the affected citrus industries has resulted in a tremendous increase to support research that in return has resulted in significant information on both applied and basic knowledge concerning this important disease to the global citrus industry. Recent research indicates the relationship between citrus and the causal agent of HLB is shaped by multiple elements, in which host defense responses may also play an important role. This review is intended to provide an overview of the importance of HLB to a wider audience of plant biologists. Recent advances on host‐pathogen interactions, population genetics and vectoring of the causal agent are discussed. Abstract : Citrus huanglongbing (HLB) is the most important disease in the citrus industry. HLB development and severity are a function of multiple elements, in which plant innate immunity, pathogen population in a specific growth region, vector spreading and jumping between regions and among hosts are major contributors.